HUBUNGAN PEMAKAIAN LUMBAR KORSET DENGAN TINGKAT NYERI PADA PASIEN HNP LUMBOSAKRAL DI UNIT REHABILITASI MEDIK RSPAD GATOT SOEBROTO PERIODE NOVEMBER 2011 - FEBRUARI 2012 - Diggivio Indrianto, (2012)
Most of the pain cases could occur in backbone of the human. One of its kind is called hernia nukleus pulposus (HNP). In the case of HNP patient, using corset could result in limited backbone movement which means corset will take the load of discus invertebralis and therefore its should be considered as a comprehensive plan for backbone pain patient's therapy. The objective of this research is to reveal the relationship of corset usage toward the pain level of HNP Lumbosakral patient. The method of the research is analytics descriptive using cross sectional research design, where data collection from independent and dependent variables conducted at the same time. This research was involving 120 patients of HNP Lumbosakral whom are undergoing a medical rehabilitation at RSPAD Gatot Subroto. The sampling technique that being used is consecutive sampling, where until the quota is reached every subjects that fulfill the requirement is involved in this research. The research's samples consist of 92 in total, which is further divided as 50 persons of corset user and 42 persons whose not. As a result of this research, there are shown that most of the patients are male (53,26%), adult (87%), and some of them was felt the pain (32%), in addition, there are also tendency of the relation between corset usage with pain level of HNP Lumbosakral patients (p = 0,014).